2006
DOI: 10.1111/j.1467-8543.2006.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Union Workers, Union Work: A Profile of Paid Union Officers in the United Kingdom

Abstract: Twelve years ago, "Working for the Union" presented an analysis of paid trade union officers working for UK unions. This paper returns to the themes of this earlier study using a fresh survey of union officers carried out in 2002. It provides limited support for two of the principal findings of the earlier research: that union work is performed differently by officers with different demographic and attitudinal characteristics and that union management systems can be effective in encouraging officers to respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…Upon request from the authors, all of the unions selected granted full access for the study. (Dundon et al, 1997;Oxenbridge, 1997) are a function of different organising methods and techniques (Heery et al, 2000a;Carter and Cooper, 2002;Oxenbridge 2000) that are in turn influenced by a number of factors such as necessary resources (Bronfenbrenner and Hickey, 2004;Heery et al, 2003b), support of union leaders (Kelly, 1998;Fiorito, 2004) and union officer commitment (Colling, 2006;Heery, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon request from the authors, all of the unions selected granted full access for the study. (Dundon et al, 1997;Oxenbridge, 1997) are a function of different organising methods and techniques (Heery et al, 2000a;Carter and Cooper, 2002;Oxenbridge 2000) that are in turn influenced by a number of factors such as necessary resources (Bronfenbrenner and Hickey, 2004;Heery et al, 2003b), support of union leaders (Kelly, 1998;Fiorito, 2004) and union officer commitment (Colling, 2006;Heery, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…While the intention of union leadership may be to move away from servicing to organising, advising and representing individual members still remains a significant part of a union official's job (Colling, 2006;Heery, 2006;Higgins, 2008;Snape, 1994). For example, Carter and Cooper (2002) noted that officials surveyed in the Manufacturing, Science and Finance Union (MSF) in Britain were unhappy with the characterization of servicing as valueless and organising as 'good' and also with the belief of key national officials that it was possible to change practice overnight.…”
Section: The Organising Model: Theory and Practicementioning
confidence: 99%
“…Thursfield (2012) found that while union officers related to traditional definitions of professionalism, the role was changing to become more managerial, despite their attempts efforts to resist such change. In practice, the managerialisation of union roles manifests itself in training and an increased emphasis on qualifications and implementation of formal organisational structures and reporting lines (Heery, 2006;Thursfield, 2012). This latter 8 dimension of managerialism also reflects practical developments and imperatives; for instance, the TUC's Leading Change training program, premised on providing management and leadership training to union officials lacking such capabilities (TUC Trades Union Congress, 2016).…”
Section: Managerialism and Trade Union Renewalmentioning
confidence: 99%
“…Such performance management systems are argued to take place within a unitarist framework (Mather and Siefret, 2011), seeking to improve performance through the measurement of achievement (Decramer, Smolders, Vanderstraeten and Christiaens, 2012). WithiIn unions, these systems have been found to broadly encompass planning, targets and the monitoring and evaluation of performance (Heery, 2003(Heery, , 2006Waddington, 2003). These developments in unions have been influenced by initiatives promoting new public management in the public sector (Dart, 2004) and encompass undertones of disciplinary practice whereby performance management is used to assess accountability to control individual behaviour (Harper and Vilkinias, 2005).…”
Section: Managerialism and Trade Union Renewalmentioning
confidence: 99%
See 1 more Smart Citation